2005
DOI: 10.1021/ef040071+
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight of Petroleum Asphaltenes:  A Comparison between Mass Spectrometry and Vapor Pressure Osmometry

Abstract: Seven asphaltene samples and six octylated asphaltene (OA) derivatives were analyzed using laser desorption ionization−time-of-flight (LDI−TOF) mass spectrometry (abbreviated as MS) and vapor pressure osmometry (VPO) techniques. Molecular weight distributions (MWDs) that were determined using MS spanned, for all asphaltenes samples and their octylated counterparts, a similar range, from ∼100 Da to ∼10 000 Da. For asphaltenes, the number-average molecular weight (M n ) and weight-average molecular weight (M w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
106
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 23 publications
(88 reference statements)
18
106
0
3
Order By: Relevance
“…The latter are the most intense signals. Figures 4 and 5 show the 13 C NMR and 1 H NMR spectra for the asphaltenes (AJ), which are similar to those previously reported by other researchers (Acevedo et al, 2005b). The adsorption of asphaltenes and other natural surfactants at the water/toluene interface has been studied here.…”
Section: Resultssupporting
confidence: 82%
“…The latter are the most intense signals. Figures 4 and 5 show the 13 C NMR and 1 H NMR spectra for the asphaltenes (AJ), which are similar to those previously reported by other researchers (Acevedo et al, 2005b). The adsorption of asphaltenes and other natural surfactants at the water/toluene interface has been studied here.…”
Section: Resultssupporting
confidence: 82%
“…Several different methods have been applied to determine the molecular mass of asphaltenes and/or their different aggregation states: vapour pressure osmometry [16], small-angle neutron and X-ray scattering (SANS and SAXS, see below), mass spectrometry [8][9][10][11][12][13][14][15][16], fluorescence depolarisation measurements [9,10], and NMR [17,18]. Mass results are different in regard to the concentration range and the measurement technique.…”
Section: Structural Information From Scattering Measurementsmentioning
confidence: 99%
“…Despite the small number and limited range of data, a regression analysis yields the following relationships: (19) [η] = 0.049M w 0.41 (20) A 2 = 0.0129M w -0.55 (21) As previously explained in Section 1, all these power law type relations could be related to mass fractal organisation of the aggregates. Comparison of relations (19,20,21) with Equations (9,16,10) large q values, is a very strong indication of the fractal nature of asphaltene aggregates. It can be concluded that asphaltene solutions in toluene are described as a polydispersion of solvated aggregates characterised by a fractal dimension close to 2.1.…”
Section: Viscositymentioning
confidence: 99%
“…Diversos trabalhos têm aplicado a osmometria de pressão de vapor (OPV) para determinações de massa molar de asfaltos e asfaltenos [9,[14][15][16][17] , pois se trata de uma técnica simples e de baixo custo [18] , apesar de os valores variarem em relação à natureza do solvente empregado [12] e à temperatura de determinação [19][20][21] . Trabalhos recentes [22][23][24] apresentaram uma forte crítica ao emprego de OPV para a determinação da massa molar de asfaltenos, sobretudo porque estas frações apresentam tendên-cia à formação de agregados mesmo em baixas concentrações.…”
Section: Descrição Do Equilíbrio Líquido-vapor Para Solução Com Solutunclassified
“…Dentre estes, asfaltenos e resinas destacam-se por serem macromolé-culas com tendência à auto-associação, o que as torna particularmente importantes para a indústria do petróleo, pois durante as diversas etapas de produção e processamento, podem tornar-se instáveis devido a variações de composição, temperatura e pressão, causando diversos problemas operacionais [2,3] . Os principais problemas relacionados aos asfaltenos são ocasionados pela floculação; formação e estabilização de emulsões e espumas; alterações na molhabilidade original do reservatório; e, principalmente, pela deposição, que consiste tipicamente em uma precipitação seguida de sedi-com os valores de massa molar dos asfaltenos obtidos pela técnica de OPV [18] . A partir de medidas de tensão superficial/interfacial, Mohamed et al (1999) [4] determinaram a concentração micelar crítica (CMC) para dois asfaltenos em solventes como tolueno, piridina e nitrobenzeno.…”
Section: Introductionunclassified